Are main clauses really ‘main’ clauses? The case of relative clauses in spoken Estonian and Finnish - Laury, Ritva; Pajusalu, Renate; Helasvuo, Marja-Liisa (UNIV TARTU PRESS, 2025)
The article concerns relative clause constructions and their main clauses in Estonian and Finnish conversation. The study shows that copula clauses and existential clauses predominate in the corpus data: these two clause types accounted for more than half of the main clauses. Such main clauses serve simply to introduce a referent which is then predicated upon in the relative clause and is likely to be subsequently discussed in the conversation. In addition, relative clauses are also used without any main clauses, headed with just a nominal, a free NP. The article thus shows that the main clauses of relative clauses in Estonian and Finnish conversation tend to be syntactically light. They are also pragmatically light, since it is the relative clause, and not the main clause, which contains the main information in the clause combination. This raises a question about the subordinate status of the relative clause.